PHOTOELECTROCHEMICAL DEHALOGENATION - BIS(CYCLOPENTA-DIENYL)-VANADIUM DICHLORIDE AND MOLYBDENUM DICHLORIDE - Compton, R; Booth, J; Eklund, J (1994)
The electrochemistry of [M(cp)2Cl2] (M = Mo or V, cp = η-C5H5) has been investigated in the presence of light of wavelengths between 300 and 400 nm. For both compounds appreciable photocurrents were found to flow at potentials more positive than those required for their oxidation. It is shown that these result from the absorption of light by the cation formed by the one-electron oxidation of [M(cp)2Cl2] and that they are mechanistically described by a photo-e.c.e (electrochemical-chemical-electrochemical) process [equations (i)-(iii)].The chemical nature of the photo induced reaction is discussed. Additionally, in the e. step [M(cp)2Cl2] - e- → [M(cp)2Cl2]+ (i), c. step [M(cp)2Cl2]+ + MeCN + hν → Cl. + [M(cp)2Cl(MeCN)]+ (ii), e. step [M(cp)2Cl(MeCN)]+ - e- → [M(cp)2Cl(MeCN)]2+ (iii) case of [V(cp)2Cl2], a parallel c.e. process also occurs as a result of the photofragmentation of the parent molecule [equations (iv) and (v)]. The kinetics and mechanism of this reaction are reported. c. step [V(cp)2Cl2] + hν → [V(cp)2Cl] + 1/2Cl2 (iv) e. step [V(cp)2Cl] - e- → [V(cp)2Cl]+ (v).